Erratum: Iridates from the molecular side - Kasper S. Pedersen (Nature Portfolio, 2016)
Nature Communications 7: Article number: 12195 (2016); Published: 20 July 2016; Updated: 31 August 2016 The original version of this Article contained an error in which the first affiliation was incorrectly given as ‘CNRS, ICMCB, UPR 9048, Pessac 33600, France’. This has now been corrected in both the PDF and HTML versions of the Article.